Muscle wasted: a novel component of the Drosophila histone locus body required for muscle integrity. - Bulchand, S.; Menon, S.D.; George, S.E.; Chia, W. (Journal of Cell Science, 2010)
Skeletal muscles arise by cellular differentiation and regulated gene expression. Terminal differentiation programmes such as muscle growth, extension and attachment to the epidermis, lead to maturation of the muscles. These events require changes in chromatin organization as genes are differentially regulated. Here, we identify and characterise muscle wasted (mute), a novel component of the Drosophila histone locus body (HLB). We demonstrate that a mutation in mute leads to severe loss of muscle mass and an increase in levels of normal histone transcripts. Importantly, Drosophila Myocyte enhancer factor 2 (Mef2), a central myogenic differentiation factor, and how, an RNA binding protein required for muscle and tendon cell differentiation, are downregulated. Mef2 targets are, in turn, misregulated. Notably, the degenerating muscles in mute mutants show aberrant localisation of heterochromatin protein 1 (HP1). We further show a genetic interaction between mute and the Stem-loop binding protein (Slbp) and a loss of muscle striations in Lsm11 mutants. These data demonstrate a novel role of HLB components and histone processing factors in the maintenance of muscle integrity. We speculate that mute regulates terminal muscle differentiation possibly through heterochromatic reorganisation.